2009
DOI: 10.1016/j.exer.2008.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Lens intermediate filaments

Abstract: The ocular lens assembles two separate Intermediate Filament systems sequentially with differentiation. Canonical 8-11 nm IFs composed of Vimentin are assembled in lens epithelial cells and younger fiber cells, while the fiber cell-specific Beaded Filaments are switched on as fiber cell elongation initiates. Some of the key features of both filament systems are reviewed.Actin filaments and microtubules are essential to the most elemental functions of eukaryotic cells. These filamentous structures are assembled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 117 publications
(140 reference statements)
1
40
0
Order By: Relevance
“…However, the possible purpose or the mechanism behind this lens barrier development in the inner cortex [74] remains unknown. Based on our present and previously published data (2,15,47] as well as inferring from reports on observations by other investigators [70,71,7577,79,8385,106,120], we hypothesize the following: The constantly growing lens has to adjust and maintain the increasing refractive index gradient, from the cortex to the nucleus, for proper focusing. To increase the refractive index, a gradual reduction in the extracellular space as well as removal of water content from both the extracellular space and cytoplasm of the mature fiber cells occur in the inner cortex and nucleus.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, the possible purpose or the mechanism behind this lens barrier development in the inner cortex [74] remains unknown. Based on our present and previously published data (2,15,47] as well as inferring from reports on observations by other investigators [70,71,7577,79,8385,106,120], we hypothesize the following: The constantly growing lens has to adjust and maintain the increasing refractive index gradient, from the cortex to the nucleus, for proper focusing. To increase the refractive index, a gradual reduction in the extracellular space as well as removal of water content from both the extracellular space and cytoplasm of the mature fiber cells occur in the inner cortex and nucleus.…”
Section: Discussionsupporting
confidence: 73%
“…The remarkable cellular rearrangements that occur in the mature fiber cells in the inner cortex and nucleus most probably could be due to dissociation of cytoplasmic N- and C-terminal ends of membrane proteins like AQP0, connexins etc., from the cytosolic proteins like crystallins and lens-specific cytoskeletal beaded filament proteins such as filensin and CP49. In order to adjust the refractive index and reduce diffraction of light in the ocular lens, fiber cells undergo a unique process of maturation by losing their nuclei as well as eliminating cellular organelles and cytoskeletal proteins; actins, intermediate filaments and beaded filaments filensin and CP49 are absent in the lens nucleus [90106]. Blankenship et al [105] showed that filensin rod domain and phakinin (CP49) localized at the membrane lining region in outer cortex cells and to the central region of the cytoplasm in inner cortex cells.…”
Section: Discussionmentioning
confidence: 99%
“…Filensin and Vimentin are major components of the intermediate filaments of the lens cytoskeleton (43). Fodrin is important in cell membrane (44).…”
Section: Discussionmentioning
confidence: 99%
“…The specialized intermediate BF cytoskeletal network is tethered to the fiber cell plasma membranes [28]. Targeted deletion of BF protein CP49 or filensin caused a dramatic loss of the highly ordered architecture of the lens [2932].…”
Section: Resultsmentioning
confidence: 99%